The effect of contextual learning approaches on student’s mathematical beliefs in junior high school - Nirfayanti Nirfayanti; A Wahid; N Afni; I R Sari (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2021)
In mathematics learning there are affective aspects that students must have. One of them is the student’s beliefs in themselves to solve the problems faced in learning mathematics. This research aim to obtain a description of the effect of the application of contextual learning approaches to mathematical beliefs of grade VII students in one of the junior high schools in Maros district, South Sulawesi province. The research adopted quantitative research and employed quasi experiment which is non-equivalent control group design. The sample of this research were 28 students of class VII.A as an experimental class and class VII.B as a control class. Data collection uses a questionnaire of 25 items to measure student’s beliefs in themselves in solving mathematical problems. Data were analysed descriptively and inferentially. Testing the hypothesis in this research using an independent sample t-test. The results showed that contextual learning applied in the experimental class could significantly influence student’s mathematical beliefs on rectangular flat figure material. This can be seen from the average score of mathematical beliefs in the experimental class students is higher than the control class. Thus the application of this contextual learning approach affects the mathematical beliefs of students